2015
DOI: 10.1002/pc.23580
|View full text |Cite
|
Sign up to set email alerts
|

Development of biowaste encapsulated polypropylene composites: Thermal, optical, dielectric, flame retardant, mechanical, and morphological properties

Abstract: Polymer matrix composites have recently gained attraction due to their light weight, low cost, and easy availability, but they are also known for their higher burning rate and low thermal stability. Polypropylene (PP) is one of the most used thermoplastic polymers, its thermal stability and flammability have been modified in this study by incorporation of oyster shell powder (OSP) into PP as a filler. Besides flammability and thermal properties, OSP incorporation has some effects on dielectric and mechanical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
9
0
2
Order By: Relevance
“…Generally, if there is no compatibility between filler powder and matrix, the tensile strength of composites decreases . Also in this study, tensile strength of OSP/PP composites was initially observed to decrease after OSP incorporation (OSPP1).…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…Generally, if there is no compatibility between filler powder and matrix, the tensile strength of composites decreases . Also in this study, tensile strength of OSP/PP composites was initially observed to decrease after OSP incorporation (OSPP1).…”
Section: Resultsmentioning
confidence: 48%
“…OSP is a flame retardant filler due to the evolution of CO 2 during its combustion, and due to the presence of mineral oxides in the seashell . In this study, all OSP/PP composites have similar concentration of OSP particles but still there is a variation in the flammability properties.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…36%, 37% and 42% in case of PA6G/20, PA6/30, and PA6G/30 composites, respectively, is observed. These results show that the huge liberation of water vapor and CO 2 species when the composite burns acting on the gas dilution fuel mechanism in the gas phase leading to an inhibition of the flame . Figure and Table also show that the PHRR is even replaced by a distinguishable plateau with the time to flame out reach 895 and 892 s for PA6/30 and PA6G/20, respectively.…”
Section: Resultsmentioning
confidence: 75%
“…In this study, an attempt has been made for the first time to focus on using waste bio‐renewable materials as fillers for the improvement of carbon composite properties and, importantly, to minimize environmental pollution. Nowadays, plastic pollution is a huge problem due to the plastic waste generated, so resources for recycling and saving materials are desperately needed; as a result, for the past decade or so, many researchers have focused on using natural resources for fabricating composites . However, the natural fibers used in natural fiber‐reinforced composites need to be compared with their traditional uses in terms of their market share.…”
Section: Introductionmentioning
confidence: 99%